2010
DOI: 10.1103/physrevlett.104.247403
|View full text |Cite
|
Sign up to set email alerts
|

Auger-Mediated Sticking of Positrons to Surfaces: Evidence for a Single-Step Transition from a Scattering State to a Surface Image Potential Bound State

Abstract: We present the observation of an efficient mechanism for positron sticking to surfaces termed here Auger-mediated sticking. In this process the energy associated with the positrons transition from an unbound scattering state to a bound image potential state is coupled to a valence electron which can then have sufficient energy to leave the surface. Compelling evidence for this mechanism is found in a narrow secondary electron peak observed at incident positron kinetic energies well below the electron work func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…In addition, the image potential sensed by the positron above a conducting surface is a highly nonlocal correlation effect, especially when positronium formation is also expected and the van der Waals interaction plays a role. Currently effects such as this can be modeled using only simple models [see, e.g., Saniz et al (2007Saniz et al ( , 2008 and Mukherjee et al (2010)]. More understanding and quantitative modeling is needed in this area as well.…”
Section: B Positron States At Interfaces and Surfacesmentioning
confidence: 99%
“…In addition, the image potential sensed by the positron above a conducting surface is a highly nonlocal correlation effect, especially when positronium formation is also expected and the van der Waals interaction plays a role. Currently effects such as this can be modeled using only simple models [see, e.g., Saniz et al (2007Saniz et al ( , 2008 and Mukherjee et al (2010)]. More understanding and quantitative modeling is needed in this area as well.…”
Section: B Positron States At Interfaces and Surfacesmentioning
confidence: 99%
“…2, a-e) are consistent with the interpretation of the VB-VB mechanism given in the discussion that follows. Here we refer to the kinetic energy of electron detected by the "fixed" analyzer as KE 1 and the energy of the electron detected by the scanned analyzer as KE 2 . If an electron detected in the fixed analyzer at energy KE 1 is below the energy of the VB photoemission peak, then it must have shared an amount of energy, ∆E, given by equation 1.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that Positron Annihilation Induced Auger Spectroscopy (PAES) can eliminate secondary electrons due to the impact of the incident beam by using a beam of positrons whose energy is below the secondary electron threshold [1]. In PAES the Auger transitions are excited through the annihilation of core electrons with positrons trapped in a surface localized state providing PAES with a high degree of surface specificity [2]. In the case of photon induced Auger excitation, Auger photoelectron coincidence spectroscopy, (APECS), originally developed by Haak and Sawatzky in 1978 [3] and adapted for a synchrotron light source by Jensen et al [4], is capable of pulling difficult to observe low energy Auger peaks out of the large background of VB photoelectrons by measuring the Auger spectra in coincidence with electrons emitted in the energy range of the peak of the photo-emitted core electron.…”
Section: Introductionmentioning
confidence: 99%
“…Previous positron lifetime experiments have shown that more than 90% of positrons implanted in a layer of PbSe QDs capped with Oleic Acid (OA) ligands trap at the surface of PbSe QDs, 16 where the positron is bound in a potential well behaving like a image potential at large distances (Figure 1). 20,21 Positrons implanted in the PbSe QD layer primarily lose their high initial kinetic energy in the PbSe cores of the QDs where they thermalize.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Therefore, the gamma rays produced by the annihilation of positrons trapped in surface states yields a way to probe the surface of PbSe QDs using 2D-ACAR, as the angular correlation of this annihilation radiation carries detailed information on the electron momentum density (EMD) sampled by the positron trapped in the surface state. 14 Films with PbSe QDs using three different ligands, namely, Oleylamine (OLA), OA and EDA, 22 were studied in order to investigate the variation in electron-positron momentum density with the type of ligand end group (amine or carboxyl) and chain length (long or short).…”
Section: Introductionmentioning
confidence: 99%